Skeletal Muscle From Myogenesis to Clinical Relations - Cseri, Julianna (IntechOpen, 2012)
The book 'Skeletal Muscle - From Myogenesis to Clinical Relations' offers a wide range of topics related to the skeletal muscle morphology and function. Chapters deal with the process of myogenesis and the regeneration of skeletal muscle as well as the morphological and functional changes on the effect of exercise or disuse. Implementation of molecular biology techniques in the investigations reveals new perspective in the understanding of skeletal muscle disorders. The deeper exploration of the neuromuscular signal transduction and modification offers more stable basis for clinical interventions. The section 'Clinical relations' highlights the background of altered muscle function in some types of myopathies and diabetes mellitus. The book is recommended to scientists, clinicians and students in the field of medical and health sciences as well as the readers who are interested in the proliferation and differentiation processes.